Pengaruh Ukuran Perusahaan, Kepemilikan Institusional Dan Intensitas Modal Terhadap Agresivitas Pajak - Eko Hadi Siswanto; Chadijah Chadijah; Nurwati Nurwati (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2021)
The phenomenon of tax aggressiveness is real, this is evidenced by the low tax ratio in Indonesia. This study aims to examine how the influence of Company Size, Institutional Ownership, and Capital Intensity on Tax Aggressiveness partially or simultaneously in infrastructure, utility, and transportation sector companies listed on the IDX in 2015-2019. This study uses secondary data in the form of financial reports obtained from the Indonesia Stock Exchange website. This research method uses quantitative research methods with data processing using Excel and the SPSS 22 program. The results of this study indicate that (1) company size has no effect on tax aggressiveness; (2) Institutional Ownership does not affect tax aggressiveness; (3) Capital Intensity affects Tax Aggressiveness; (4) Company Size, Institutional Ownership, and Capital Intensity together affect Tax Aggressiveness with the value of the Adjusted R Square coefficient of determination of 42.7%.